1999
DOI: 10.1046/j.1523-1747.1999.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Epidermal T Cells in Psoriasis Vulgaris Lesions can Produce Type 1 Cytokines, Interferon-γ, Interleukin-2, and Tumor Necrosis Factor-α, Defining TC1 (Cytotoxic T Lymphocyte) and TH1 Effector Populations:1 a Type 1 Differentiation Bias is also Measured in Circulating Blood T Cells in Psoriatic Patients

Abstract: Psoriasis vulgaris is a skin disease potentially mediated by pro-inflammatory cytokines produced by type 1 lesional T cells. The capability of individual T cells to produce these cytokines in lesional skin is not known. In this study we measured the ability of lesional and peripheral blood T cells to produce intracellular interferon-gamma, tumor necrosis factor-alpha, interleukin-2, interleukin-4, and interleukin-10 proteins as detected by flow cytometric analysis. Cytokine synthesis was induced by activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
303
0
20

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 452 publications
(337 citation statements)
references
References 63 publications
14
303
0
20
Order By: Relevance
“…However, this is the first report to demonstrate that anti-IL-12p40 administration to psoriasis patients down-regulates type 1 cytokines, chemokines and also IL-12/IL-23 themselves in lesional skin. It has been shown that IFN-␥ mRNA expression is elevated in psoriatic skin lesions and the lesions are infiltrated by numerous IFN-␥-producing T cells (13,15,17). In this study, the levels of IFN-␥ expression in the lesional skin was reduced in almost all patients, as early as 2 wk after anti-IL-12p40 administration (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, this is the first report to demonstrate that anti-IL-12p40 administration to psoriasis patients down-regulates type 1 cytokines, chemokines and also IL-12/IL-23 themselves in lesional skin. It has been shown that IFN-␥ mRNA expression is elevated in psoriatic skin lesions and the lesions are infiltrated by numerous IFN-␥-producing T cells (13,15,17). In this study, the levels of IFN-␥ expression in the lesional skin was reduced in almost all patients, as early as 2 wk after anti-IL-12p40 administration (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Many studies examining the cytokine profile of T cells derived from psoriatic lesions suggest that the type 1 cytokine-producing T cell subset is a prominent component of the lesions (13)(14)(15)(16)(17). Psoriatic lesions showed elevated mRNA expression for type 1 cytokines (IFN-␥, IL-2, and TNF-␣), compared with lesion-free psoriatic skin and normal skin, without a significant component of type 2 cytokines (IL-4, IL-5, and IL-10) (18).…”
mentioning
confidence: 99%
“…It is also indicated that these gangliosides may be involved in the development of diseases with Th1/Th2 imbalance. Rheumatoid arthritis, multiple sclerosis, and psoriasis are inflammatory diseases characterized by Th1-skewed immunity; T cells from patients with these diseases predominantly produce Th1-type cytokines, such as IFN-␥, over Th2 (55)(56)(57), indicating the increase of GD1b, GT1b, or GQ1b in the patients' sera. In contrast, T cells from patients with atopic dermatitis or asthma produce abnormally high amounts of Th2 cytokines in response to allergens or mitogens while Th1 responses are suppressed (58,59), indicating the decrease of GD1b, GT1b, or GQ1b in the patients' sera.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have suggested a predominance of type 1 (Th1 and Tc1 T cell subset)-associated cytokines, such as interferon (IFN)-␥ and interleukin (IL)-2, within psoriatic lesions. 2,3 Xenotransplantation experiments involving grafting of nonlesional skin from psoriatic patients to immunodeficient mice and the subsequent introduction of autologous, stimulated immunocytes to induce plaque formation 4 have demonstrated the obligatory role of these cells in the pathology. Further, many effective antipsoriatic therapies, including cyclosporin A, alefacept, and efalizumab, directly target T cells as their major mode of action.…”
mentioning
confidence: 99%